Study of the Astrophysically Important States in 26 Si via the p(27Si,d)26 Si* Reaction and the p(25Al,p )^25Al Elastic Scattering - Chen, Jun (My University, 2009)
The radioactive 26Al is an important probe for the interstellar medium of our galaxy since it is observed through the emission of 1.8 MeV gamma rays from the decay of 26gAl produced by the proton capture on 25Mg. But the production of the galactic 26Al is now still not well determined partially due to the lack of knowledge of the important states in 26Si which dominate the large uncertainty in the 25 Al(p,γ)26Si reaction rate at nova temperatures.
In nova explosions, the proton capture of 25Al competes with its β decay and bypasses the production of 26gAl, since the capture product 26Si decays quickly to 26mAl instead of its ground state, without the emission of the 1.8 MeV gamma ray. But at even higher temperatures, such as in supernova explosions, 26mAl can be excited to the higher excited states by thermal excitation and then quickly de-excite to the ground state, thereby enhancing the production of 26gAl. The energy levels in 26Si in the Gamow window corresponding to these temperatures therefore need to be well understood in order to determine the 25Al(p,γ)26Si reaction rate, and thus the production rate of 26Al in these explosive environments.
Two experiments were performed to study the important states in 26Si : one is the p(27Si,d)26Si* reaction at the NSCL, aiming to construct the level scheme of low lying states around the proton threshold; the other experiment is a measurement of the elastic scattering of 25Al+p with CRIB at RIKEN in order to obtain information on states in a broad range above the proton threshold. Details of these two experiments and their data analyses will be presented in this thesis.
Keywords: 26Al, states, elastic, scattering, reaction, rate, 26Si